Theoretical and experimental study of motion suppression and friction reduction of rotor systems with active hybrid fluid-film bearings. (1st January 2023) - Li, Shengbo; Zhou, Changjiang; Savin, Leonid; Shutin, Denis; Kornaev, Alexey; Polyakov, Roman; Chen, Zhaobo
Graphical abstract: Highlights: Active hybrid bearings (AHB) are studied theoretically and experimentally. An approach to joint friction and motion control of rotor with AHBs is described. A nonlinear adaptive P-controller is used in AHBs for rotor vibrations suppression. Viscous friction in AHBs is reduced by adjusting setpoint in rotor position controller. Static and dynamic effects of viscous friction reduction are studied. Abstract: Active bearings (including fluid film bearing) are efficient in reducing vibration and improving dynamic performances of rotary machinery. The control systems have significant influence in the working processes of rotor-bearing systems, including hydrodynamic and tribological performance. The aim of the study is to investigate the feasibility of the joint controlling of the rotor vibration and simultaneously minimizing friction losses in active hybrid bearing (AHB) – rotor systems. The theoretical and experimental results show the rotor vibrations are reduced at the energy-efficient operating modes under complex loads. The theoretical study is performed by the verified simulation models of rigid rotors with thrust and journal AHB. The artificial neural networks are proposed to calculate the bearing forces to provide a balance of accuracy and computational costs. The controller for the thrust AHB is based on the PI law, while the journal AHB controller implements an adaptive nonlinear proportional law with integrating properties. Both controllers perform well in reducing the vibration magnitudes for the systems under the periodic and constant load forces. Such rotor motion control is also able to reduce power losses caused by the viscous friction in AHB. The theoretical study shows the relations between the position of the rotor with AHBs and the magnitude of the viscou forces of the lubricant film. The minimum friction areas could be used to choose the setpoints for AHBs' controllers for joint rotor motion and friction control.